Intraempreendedorismo e governança pública: a relação entre o comportamento empreendedor e o desempenho da governança na gestão pública municipal - Silva, Marcus Vinicius Gonçalves da (2017)
The scope of this research is to analyze the level of entrepreneurship of the political agents that occupy positions of leadership, direction and advising, in the city hall and its autarchies, located in a city from the north-central region of the state of Paraná, intending to verify if the Behavioral characteristics of managers has any influence on the performance of public governance. This analysis is part of an embryonic field of study in the area of public management in Brazil, both in the field of entrepreneurship in the public sector and in the availability and use of tools to evaluate municipal public governance. In this context, two instruments were used: i) Carland Entrepreneurship Index (CEI), by Carland, Carland and Hoy (1992); And, ii) PISA's Public Governance Index (IGovP) (2014). The methodological procedures are classified, as to the purpose, in applied research; As to the method a case study; With respect to the research problem it has a qualitative approach; The research is exploratory and descriptive; And regarding to procedures it is characterized as bibliographical and documentary; With primary data sources obtained through field surveys; And, secondary, according to the availability of the data in the official websites from the city hall, the state of Paraná and, the federal government. The results reveal that in the CEI categorization, public managers presented themselves as entrepreneurs and in the performance of public governance measured by IGovP, the city presented an average performance in the governance index. Moreover, it remains evident that the entrepreneurial behavior of political agents can influence the performance of public governance.